Repeated kidney re‐transplantation—the Eurotransplant experience: a retrospective multicenter outcome analysis. (30th January 2020) - Assfalg, Volker; Selig, Katharina; Tolksdorf, Johanna; van Meel, Marieke; de Vries, Erwin; Ramsoebhag, Anne‐Marie; Rahmel, Axel; Renders, Lutz; Novotny, Alexander; Matevossian, Edouard; Schneeberger, Stefan; Rosenkranz, Alexander R.; et al.
Summary: In Eurotransplant kidney allocation system (ETKAS), candidates can be considered unlimitedly for repeated re‐transplantation. Data on outcome and benefit are indeterminate. We performed a retrospective 15‐year patient and graft outcome data analysis from 1464 recipients of a third or fourth or higher sequential deceased donor renal transplantation (DDRT) from 42 transplant centers. Repeated re‐DDRT recipients were younger (mean 43.0 vs. 50.2 years) compared to first DDRT recipients. They received grafts with more favorable HLA matches (89.0% vs. 84.5%) but thereby no statistically significant improvement of patient and graft outcome was found as comparatively demonstrated in 1st DDRT. In the multivariate modeling accounting for confounding factors, mortality and graft loss after 3rd and ≥4th DDRT ( P  < 0.001 each) and death with functioning graft (DwFG) after 3rd DDRT ( P  = 0.001) were higher as compared to 1st DDRT. The incidence of primary nonfunction (PNF) was also significantly higher in re‐DDRT (12.7%) than in 1st DDRT (7.1%; P  < 0.001). Facing organ shortage, increasing waiting time, and considerable mortality on dialysis, we question the current policy of repeated re‐DDRT. The data from this survey propose better HLA matching in first DDRT and second DDRT and careful selection of candidates, especially for ≥4th DDRT.